ASSESSMENT OF CONGENITAL HEART DISEASE AND RELATED VARIOUS FACTORS IN THE NEONATES OF MOTHERS WITH DIABETES - Hina Khalid (Army Medical College Rawalpindi, 2020)
Objective: To assess the frequency of congenital heart disease and its association with various factors in neonates of mothers with diabetes.